2021
DOI: 10.3390/jcm10051102
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, Labor-Time and Patient-Reported Outcomes with Partially versus Fully Digital Workflow for Flapless Guided Dental Implants Insertion—A Randomized Clinical Trial with One-Year Follow-Up

Abstract: (1) Background: Prosthetically-driven implant positioning is a prerequisite for long-term successful treatment. Transferring the planned implant position information to the clinical setting could be done using either static or dynamic guided techniques. The 3D model of the bone and surrounding structures is obtained via cone beam computed tomography (CBCT) and the patient’s oral condition can be acquired conventionally and then digitalized using a desktop scanner, partially digital workflow (PDW) or digitally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Apart from the few comparative studies, 17 studies reported survival rates of implants placed with different static or d‐CAIS protocols. Fourteen of these studies had a follow‐up of at least 1 year, one was 3 months, 30 while in the other two, 28,31 the observation period was not reported. Among these, eight studies reported 100% survival of the implants without complications 15,25,30–35 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the few comparative studies, 17 studies reported survival rates of implants placed with different static or d‐CAIS protocols. Fourteen of these studies had a follow‐up of at least 1 year, one was 3 months, 30 while in the other two, 28,31 the observation period was not reported. Among these, eight studies reported 100% survival of the implants without complications 15,25,30–35 .…”
Section: Methodsmentioning
confidence: 99%
“…Five studies reported implants without osseointegration after completion of the healing period, all of which concerned s‐CAIS placement 13 , 15 , 18 , 23 , 28 (Table 4 ). Failure of osseointegration in cases of conventional loading 18 , 23 , 28 was reported in 0.69%‐3.23% of the implants placed, affecting 1.52%‐9.09% of patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Image J open software (https://imagej.nih.gov/; accessed on 13 September 2021), calibrated for each measurement based on the known implant length [16], was used to measure the peri-implant marginal bone level at mesial and distal sites, on the panoramic radiographs at prosthetic insertion and at 1-year post loading. For calibration with the known implant length, the reference points were implant apex and implant collar.…”
Section: Evaluation Of 1-year Bone Remodellingmentioning
confidence: 99%
“…Before any radiological examination, a film holder was directly customized in the patient's mouth using auto-polymerizing acrylic resin to reproduce the same position of the film, thereby obtaining superimposable dental radiographs at different time intervals. Bone level was measured on digital radiographs using Image J open software (imagej.nih.gov, accessed on 28 July 2021), calibrated for each measurement based on the known implant length [24]. For calibration with the known implant length, the reference points were implant apex and implant collar, and for mesial and distal bone level measurements, the reference points were the correspondent horizontal point of the implant apex and the most coronal bone to implant contact.…”
Section: Peri-implant Marginal Bone Lossmentioning
confidence: 99%